The Importance of the Family in Forming a Healthy World View - Muqaddas Rakhimjanova (Zien Journals, 2023)
The role of the family, youth education, emerging problems, causes and solutions in turning a healthy worldview and creativity into a nationwide movement are mentioned in the article.
Keywords: Family; Hadith; Child Upbringing; Healthy Outlook